2023
DOI: 10.7150/ijms.78590
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Immune Infiltration Value of Proteasome Assembly Chaperone (PSMG) Family Genes in Lung Adenocarcinoma

Abstract: The complexity of lung adenocarcinoma (LUAD) including many interacting biological processes makes it difficult to find therapeutic biomarkers for treatment. Previous studies demonstrated that PSMG (proteasome assembly chaperone) family members regulate the degradation of abnormal proteins. However, transcript expressions of this gene family in LUAD still need to be more fully investigated. Therefore, we used a holistic bioinformatics approach to explore PSMG genes involved in LUAD patients by integrating seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…The key gene SLIT3 encodes a protein that is secreted and may interact with the circuitous homologue receptor to in uence cell migration, and it was conjectured that the effect of macrophage-secreted protein SLIT3 in activating beige adiposity might relevant to the progression of BPH [21]. It has been reported that the overexpression of PSMG4 in tumor tissues can promote the development of tumors and the proliferative ability of cancer cells [22], which may also be a potential gene affecting the occurrence and development of BPH. The key gene TCF21 is a gene encoding transcription factor 21 and a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…The key gene SLIT3 encodes a protein that is secreted and may interact with the circuitous homologue receptor to in uence cell migration, and it was conjectured that the effect of macrophage-secreted protein SLIT3 in activating beige adiposity might relevant to the progression of BPH [21]. It has been reported that the overexpression of PSMG4 in tumor tissues can promote the development of tumors and the proliferative ability of cancer cells [22], which may also be a potential gene affecting the occurrence and development of BPH. The key gene TCF21 is a gene encoding transcription factor 21 and a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis from TCGA highlights NORAD as the central regulator for regulon reconstruction, revealing a network of co-expression with genes potentially modulated by NORAD, some of them being PUM target genes, such as the proteasome assembly chaperone 4 (PSMG4) [45], a proteasome assembly chaperone protein upregulated in lung neoplastic cells and correlated with poor prognosis [74]. NORAD regulon showed a positive activity in ER+ and PR+ tumors but was inactive in BL tumor samples.…”
Section: Norad Higher In Low Cd8 T-cell Count; the Promotion Of Malig...mentioning
confidence: 99%